Genomic organization and evolution of the 5S ribosomal DNA in Tilapiini fishes - Alves-Costa, F. A.; Wasko, A. P.; Oliveira, C.; Foresti, F.; Martins, C. (Springer, 2006)
5S rDNA sequences present an intense dynamism and have proved to be valuable as genetic markers to distinguish closed related species and also in the understanding of the evolutionary dynamic of repetitive sequences in the genomes. In order to identify patterns of 5S rDNA organization and their evolution in the genome of fish species, such genomic segment was investigated in the tilapias Oreochromis niloticus and Tilapia rendalli, and in the hybrid O. urolepis hornorum x O. mossambicus. A dual 5S rDNA system was identified in the three analyzed tilapia samples. Although each 5S rDNA class was conserved among the three samples, a distinct 5S rDNA genome organization pattern could be evidenced for each sample. The presence of a dual 5S rDNA system seems to be a general trait among non-related teleost fish orders, suggesting that evolutionary events of duplication have occurred before the divergence of the main groups of teleost fishes.
Keywords: Cichlidae; fish; NTS; Oreochromis; 5S rDNA; Tilapia; tilapia